Large-scale drivers of the exceptionally low winter Antarctic sea ice extent in 2023 - Ionita, Monica (Frontiers in Earth Science, 2024)
The year 2023 marked a turning point for the Antarctic region as the Southern Hemisphere experienced a significant reduction in its sea ice extent, with a record-breaking sea ice minimum in July 2023 of approximately 2.4 million square kilometers below the long-term average. This study highlights the drivers behind this exceptional event by combining observational, satellite, and reanalysis data, with a special focus on the large-scale atmospheric circulation. Throughout the year, the Antarctic Sea ice extent broke record after record, ranking as the lowest sea ice on record from January to October, except for March and April. The exceptionally low sea ice extent from May to August was mainly driven by the prevalence of a zonal wave number 3 pattern, characterized by alternating surface high- and low-pressure systems, which favored the advection of heat and moisture, especially over the Ross Sea (RS), Weddell Sea (WS), and Indian Ocean (IO). The anomalous large-scale circulation was accompanied by record-high sea surface and subsurface temperatures over the regions with reduced sea ice extent. In addition to the air and ocean temperature, record-breaking heat, moisture, and sensible heat fluxes have been observed, especially over the WS, RS, and IO, which further amplified the reduction in the sea ice extent over these areas. Notably, over the Weddell Sea, we observed air temperature anomalies reaching up to 8°C and sea surface temperature anomalies of up to 3°C from May to July. Similar temperature anomalies were recorded over the Ross Sea, particularly in July and August. A change point analysis indicates that a regime shift in the Antarctic Sea ice, as well as in the average mean air temperature and (sub)surface ocean temperature over the Weddell Sea, started around 2015. The low sea ice extent in Antarctica in 2023 was a stark reminder of the ongoing changes in the polar regions. Thus, understanding the underlying mechanisms of these extreme events provides crucial insights into the changing dynamics of Antarctic Sea ice and its broader climatic significance.